2022
DOI: 10.1039/d2sc02448a
|View full text |Cite
|
Sign up to set email alerts
|

N-Cyanorhodamines: cell-permeant, photostable and bathochromically shifted analogues of fluoresceins

Abstract: N-Cyanorhodamines – photostable, cell-permeant analogues of fluoresceins – provide fast labelling kinetics with the HaloTag protein and background-free images in multicolour super-resolution microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 60 publications
(71 reference statements)
0
9
0
Order By: Relevance
“…Hell and coworkers replaced the N-alkyl groups with cyano substituents, resulting in negatively charged dyes such as CR1, which, while spectrally comparable to TMR, can show less offtarget labelling inside cells. [35] Alkylation at other positions on rhodamines has been scarcely reported. However, it was recently shown that replacement of the methyl groups on the central Si atom of SiR could result in a small red-shift and increase in brightness while providing an alternative position to append functional groups including the HaloTag ligand.…”
Section: Rhodamine-based Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hell and coworkers replaced the N-alkyl groups with cyano substituents, resulting in negatively charged dyes such as CR1, which, while spectrally comparable to TMR, can show less offtarget labelling inside cells. [35] Alkylation at other positions on rhodamines has been scarcely reported. However, it was recently shown that replacement of the methyl groups on the central Si atom of SiR could result in a small red-shift and increase in brightness while providing an alternative position to append functional groups including the HaloTag ligand.…”
Section: Rhodamine-based Ligandsmentioning
confidence: 99%
“…Other modifications of the rhodamine scaffold and their use as HaloTag ligands have been recently reported and further diversify their photophysical and biochemical properties. Hell and coworkers replaced the N ‐alkyl groups with cyano substituents, resulting in negatively charged dyes such as CR1, which, while spectrally comparable to TMR, can show less off‐target labelling inside cells [35] . Alkylation at other positions on rhodamines has been scarcely reported.…”
Section: Fluorescent and Fluorogenic Ligands For Halotag Protein Labe...mentioning
confidence: 99%
“…Therefore, the development of new and improved fluorescent compounds is crucial for the continued advancement of biomedical imaging, as well as the diagnosis and treatment of various diseases. 8 This article is licensed under CC-BY-NC-ND 4 In this regard, great effort has been made in developing new fluorophores with improved properties from classical scaffolds, the majority of these are created through structural alterations of a small number of classical "core" dyes, 9 including naphthalimide, 10 coumarin, 11 BODIPY, 6 fluorescein, 12 and rhodamine. 13 However, the creation of new "core" fluorophores could provide greater versatility and flexibility for developing novel fluorescent probes with unique properties.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, great effort has been made in developing new fluorophores with improved properties from classical scaffolds, the majority of these are created through structural alterations of a small number of classical “core” dyes, 9 including naphthalimide, 10 coumarin, 11 BODIPY, 6 fluorescein, 12 and rhodamine. 13 However, the creation of new “core” fluorophores could provide greater versatility and flexibility for developing novel fluorescent probes with unique properties.…”
Section: Introductionmentioning
confidence: 99%
“…The former two primarily allow for high signal-to-noise ratios, while the latter two allow for dynamic and targeted examinations. Most commercial and published fluorescence bioprobes, such as anthocyanins, 25 fluoresceins, 26 rhodamines, 27 and boron dipyrromethenes, 28 belong to the aggregation-caused quenching (ACQ) type fluorophore, and the aggregation-induced emission (AIE) ones are flourishing as the next-generation fluorophore. [29][30][31][32][33][34][35] However, it is worth noting that both ACQ-and AIE-active fluorescence bioprobes still suffer from concentration-dependent erroneous signal reading in practical bioimaging, even leaving aside the above four requirements.…”
Section: Introductionmentioning
confidence: 99%